Optimization of nifedipine loaded gastroretentive microcapsules for biliary colic - Sultana, Shaheen; Talegaonkar, Sushma; Bhatnagar, Aseem; Ahmad, Farhan J; Mittal, Gaurav (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this research work was to formulate and systematically evaluate in vitro performance of gastroretentive microcapsules of nifedipine for biliary colic. Crossâ€linked reinforced alginateâ€chitosan microcapsules were prepared by ionotropic gelation method using calcium chloride (CaCl2) as a crossâ€linking agent. The microcapsules were evaluated for physical characteristics such as particle size, particle shape and surface morphology by scanning electron microscopy, drug entrapment efficiency, in vitro drug release and in vitro bioadhesion studies. Results of preliminary trials indicated that the polymer concentration, crossâ€linking agent and chitosan had a noticeable effect on size and surface morphology. A Boxâ€Behnken design was employed to study the effect of independent variables, polymer concentration (X1), CaCl2 concentration (X2), chitosan (X3) and pH of encapsulation medium (X4) on dependent variables, drug entrapment efficiency and percentage drug release respectively.The entrapment efficiency varied from 6.14 to 79.21% depending upon the independent variables.The release can be sustained for more than 7 hours for all batches. It was observed that polymer and crossâ€linker concentration had a more significant effect on the dependent variables.Validation of optimization study, performed using 6 confirmatory runs, indicated very high degree of prognostic ability of response surface methodology, with mean percentage error (Â± SD) as â€0.85 Â± 4.39% and 2.83 Â± 2.91% for drug entrapment and drug release. Optimization was done on the basis of maximum entrapment (82.26%) which was predicted using 6% alginate, 8.11% CaCl2, 2% chitosan at a pH of 3.55 of encapsulation medium.The optimized formulation depicted a release of 57.17% at 7 hours. Point prediction tool of design expert software shows 101.91% and 96.82% validity of the predicted model for drug entrapment and percent drug release. The release follow Higuchi kinetics followed by nonâ€fickian diffusion process. In vitro wash off test showed 71% bioadhesion after 1 hour.